High Performance N-Doped Carbon Electrodes Obtained via Hydrothermal Carbonization of Macroalgae for Supercapacitor Applications (2018)
ABSTRACT: The conversion of bio-waste into useful porous carbons constitutes a very attractive approach to contribute to the development of sustainable energy economy, even more as they can be used in energy storage devices. Here we report the synthesis of N-doped carbons from hydrothermal carbonization of macroalgae, Enteromorpha prolifera (EP), followed by a mild KOH activation step. The obtained N-doped carbons exhibited surface areas of up to ~2000 m2/g with N-loadings varied in the range of 1.4~2.9 at%. By modifying activation temperature, we were able to tune the surface chemistry and porosity, achieving excellent control of their properties. The specific capacitance reached values of up to 200 F/g at 1 A/g in 6 M KOH for the sample obtained at activation temperature of 7008C (AHC-700). The symmetric supercapacitor using the sample activated at 8008C (AHC-800) as electrodes exhibited the highest cycling stability of the samples studied in this work, with capacitance retention of up to 96% at 10 A/g, even after 10,000 cycles, constituting the highest reported for biomass-derived carbon electrodes. These results show the great potential of N-doped carbons as electrodes for supercapacitors and confirm the excellent electrochemical properties of biomass-derived carbons in energy storage technologies.